Expressão gênica e potencial de desenvolvimento in vitro dos complexos cúmulos-oócitos ovinos tratados com roscovitina - Crocomo, Letícia Ferrari [UNESP] (2015)
This study aimed to evaluate the expression profile of certain genes and the potential of in vitro development of sheep cumulus-oocytes complexes (COCs) temporarily arrested at germinal vesicle (GV) stage using roscovitine. In this context, different medium compositions (with and without fetal bovine serum and gonadotropins), times (0, 6, 12 and 20 hours) and methods of culture (with and without mineral oil overlay) were tested in order to ensure maximum efficiency of meiotic inhibition promoted by 75μM roscovitine. The evaluation of cumulus expansion degree, under stereomicroscope, and nuclear maturation stage, by staining with Hoechst 33342, revealed that the presence or absence of LH, FSH and fetal bovine serum did not influence the action potential of roscovitine. However, maximum efficiency of meiotic inhibition was observed in medium supplemented with fetal bovine serum. It was also found that, in the absence of mineral oil overlay, significantly higher quantity of oocytes treated with roscovitine was kept at GV, which reinforces the hypothesis of liposolubility of this inhibitor. Although the potential of meiotic inhibition of roscovitine had remained at different culture times, the prolonged exposure of COCs to inhibitor irreversibly affect the cumulus expansion. In all cases, the meiotic arrest was completely reversible after culture for a further 18 h in inhibitor-free medium. Therefore, for analysis of gene expression and in vitro embryo development, it was chosen the treatment with 75μM roscovitine for 6 h under serum-supplemented medium and without mineral oil overlay. Under these conditions as well as after the reversibility for 18 h, the relative amount of most investigated genes in cumulus cells and oocytes was similar to that observed in the uninhibited COCs (control). Similarly, no difference was found between roscovitine treatment and control with respect to blastocyst rate and quality of embryos obtained. Therefore, ...